2004
DOI: 10.1001/archpedi.158.10.956
|View full text |Cite
|
Sign up to set email alerts
|

Child Neurodevelopmental Outcome and Maternal Occupational Exposure to Solvents

Abstract: In utero exposure to organic solvents is associated with poorer performance on some specific subtle measures of neurocognitive function, language, and behavior. Reducing exposure in pregnancy is merited until more refined risk assessment is possible. Further studies that address exposure to specific solvents, dose, and gestational timing of exposure are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 12 publications
4
61
0
2
Order By: Relevance
“…Attainment of early developmental milestones is delayed by prenatal exposure to toluene as typically assessed by performance on a battery of physical, motor, and other neurobehavioral outcomes. There were no significant differences in age to reach developmental milestones up to 4 years of age (e.g., first sit, crawl, walk, etc) in children of 32 women exposed to one or more of two dozen different solvents at work -of which toluene was the most common [Laslo-Baker et al 2004]. In clinical studies of toluene ''abuse'', developmental delay was reported in 80% of infants born to tolueneabusing mothers [Hersh et al 1985;Hersh 1989;Wilkins-Haug and Gabow 1991;Arnold et al 1994;Pearson et al 1994;Arai et al 1997;Wilkins-Haug 1997].…”
Section: Pregnancy Outcomesmentioning
confidence: 83%
“…Attainment of early developmental milestones is delayed by prenatal exposure to toluene as typically assessed by performance on a battery of physical, motor, and other neurobehavioral outcomes. There were no significant differences in age to reach developmental milestones up to 4 years of age (e.g., first sit, crawl, walk, etc) in children of 32 women exposed to one or more of two dozen different solvents at work -of which toluene was the most common [Laslo-Baker et al 2004]. In clinical studies of toluene ''abuse'', developmental delay was reported in 80% of infants born to tolueneabusing mothers [Hersh et al 1985;Hersh 1989;Wilkins-Haug and Gabow 1991;Arnold et al 1994;Pearson et al 1994;Arai et al 1997;Wilkins-Haug 1997].…”
Section: Pregnancy Outcomesmentioning
confidence: 83%
“…For each article, the following information was abstracted: location, type of study, study period, population, child age, type of exposure, exposure measurements, covariates, outcome scales, and effects studied. Through this systematic search, a total of 15 papers 23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] were identified that fit the above criteria (Table 1). Each of these studies is reviewed below.…”
Section: Review Strategymentioning
confidence: 99%
“…They are lipophilic and are mostly known to be neurotoxic from acute poisoning cases and occupational studies in adults with chronic exposure 2) . Seven epidemiological studies have assessed the neurodevelopmental consequences in children of workers with solvent exposures during pregnancy (Table 1) 23,[25][26][27][28][29][30] .…”
Section: Organic Solventsmentioning
confidence: 99%
See 2 more Smart Citations